2021
DOI: 10.1007/s00436-021-07261-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution of Acanthamoeba in keratitis: a systematic review

Abstract: Acanthamoeba spp. are among the most worldwide prevalent protozoa. It is the causative agent of a disease known as Acanthamoeba keratitis, a painful and severe sight-threatening corneal infection that can lead to blindness. In recent years, the prevalence of Acanthamoeba keratitis has rapidly increased, growing its importance to human health. This systematic review aims to assess the distribution of Acanthamoeba sp. genotypes causing keratitis around the world, considering the sample collected type and the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 123 publications
1
23
0
Order By: Relevance
“…1 ). Only 1/7 strain belonged to the T3 genotype, while 6/7 strains were clustered near genotype T4 of Acanthamoeba spp., which, to the best of our knowledge, was the most representative of infections in both keratitis and nonkeratitis samples ( 32 ). Moreover, strains of the T4 genotype were clustered in three subtypes (T4A, T4D, T4E), which indicated that they may difference in pathogenicity and virulence.…”
Section: Resultsmentioning
confidence: 96%
“…1 ). Only 1/7 strain belonged to the T3 genotype, while 6/7 strains were clustered near genotype T4 of Acanthamoeba spp., which, to the best of our knowledge, was the most representative of infections in both keratitis and nonkeratitis samples ( 32 ). Moreover, strains of the T4 genotype were clustered in three subtypes (T4A, T4D, T4E), which indicated that they may difference in pathogenicity and virulence.…”
Section: Resultsmentioning
confidence: 96%
“…1,28,29 We did not examine the species or genotypes of Acanthamoeba isolates (consistent with routine practice in most clinical microbiology laboratories), although we acknowledge that the species of clinical Acanthamoeba isolates may be associated with susceptibility. 21,30,31 Finally, although the isolates included in the study should be broadly representative of AK in the 2 study locations, the generalizability of the results to other locations is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Most isolates of Acanthamoeba spp. reported as pathogens are distributed among the T5, T11, T15, T3, and T4 genotypes, and among them, the T4 genotype is more prevalent in hot springs (Mahmoudi et al 2015 ; Fabros et al 2021 ) and is associated with most cases of Acanthamoeba keratitis (Diehl et al 2021 ; Bellini et al 2022 ). The presence and abundance of FLA in swimming pool water clearly indicate that in addition to these microorganisms being resistant to chlorine in the dosage used in the treatment of drinking water (Thomas et al 2004 ; Majid et al 2017 ; Gomes et al 2020 ), they are also resistant to chlorine and other disinfectants in the dosage used for swimming pools and artificial recreational waters (Rivera et al 1983 ; Kiss et al 2014 ; Zeybek et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%